Psicologia sócio-histórica e formação continuada de professores em serviço: revisão integrativa de estudos de 2005 a 2020 - Carvalho, Agda Malheiro Ferraz de (2020)
The present work aims to carry out an integrative review, identifying and analyzing scientific articles that dealt with teachers' continuing education from the cultural-historical psychological approach. We mapped, according to SciELO, the five most consulted education journals during the years 2009 to 2019, as well as four Qualis A1 ones, from 2005 to 2020. Justifies this study the fact that that this approach has begun to be studied in Brazil in the 1980s, more than 40 years ago, time enough to be sedimented and used in continuing teacher education. We were able to locate nine articles containing the terms "continuing education", "teacher education", "teacher education", "professional development", associated with the words: cultural-historical psychology," "socio-historical psychology," and "Vigotski," in the title, abstract and keywords. The analysis treated the article grouping them into seven themes: 1) objectives of the articles; 2) keywords; 3) strategies used in training; 4) relationship between initial and continuing education; 5) the role of the trainer; 6) mention to public policies and 7) names of the most cited authors in the references. Most of the articles were empirical and from the area of Education; others seek to explain ways of conducting continuing education in service. Still, others deal with continuing education, mentioning certain concepts arising from socio-historical psychology. There was no consensus among the authors on the socio-historical perspective, and one article even proposed a new meaning for the ZDP. Even if this has not been a guide to teachers' continuous education, the PSH could be adequate to change teachers' views about the human constitution, proposing a new view school, student, teacher, and society. As the teacher's role in the educational process is central to the students' learning, this is more than necessary to provide a genuinely inclusive and good quality education for those presently enrolled in Basic Education